Margaret Thatcher is my sister: Counselling on divisions between women - Itzin, Catherine (Women's Studies International Forum, 1985)
This paper looks at the ways in which women are divided from themselves and each other as women: at the internalised oppression which results from THE oppression of patriarchy, at the systematic mistreatment of women as a group by men as a group reinforced by the social structures of male power. It also looks at the ways in which women are divided from each other as a result of other oppressive systems such as class and/or race or religion or physical ability or age. The paper then describes how the particular theory and practice of Re-evaluation Counselling can be used to ‘deconstruct’ or ‘discharge’ the internalised oppression of patriarchy and other oppressive systems, making the principles of Women's Liberation and sisterhood a practical possibility for ‘everywoman’ and all women—including Margaret Thatcher. Throughout, the word ‘patriarchy’ is used to mean the system of male power usually regarded as synonymous with sexism.
Keywords: approches et analyses; capacitisme; militance; patriarcat; racisme; sororité; systèmes d'oppressions; thématiques; âgisme

Virgile, non - Wittig, Monique (Les Éditions de Minuit, 1985)
Imaginez l'espace d'un film de Cocteau quand les personnages remontent le temps et se déplacent au ralenti, à cause de la force du vent. C'est dans un tel univers visuel que l'auteure de ce livre, devenue personnage à son tour, va et vient. Le lieu imaginé cependant n'a pas pour référence l'antiquité et les vieux murs mais le San Francisco moderne. C'est un San Francisco rendu utopique par la projection systématique d'un nulle part qui est soit l'enfer, soit les limbes, soit le paradis. Dans l'enfer souffle le vent et il est difficile d'avancer. Dans le paradis on tombe sans crier gare. Quant aux limbes c'est là où on va boire un coup. On, c'est-à-dire Wittig et Manastabal, un guide qui est loin d'avoir la douceur du Virgile de Dante, protagonistes d'un opéra des gueuses à la fois féroce et gai et qui comme la comédie de Dante finit bien. Il y a une providence, il y a des anges en chair et en os, il y a des monstres, il y a l'Achéron, il y a les horreurs de l'enfer et les délices du paradis. Ce texte est paru en 1985.
Keywords: approches et analyses; droits des femmes*; lesbianisme; militance; personnes lesbiennes; roman; sexisme; systèmes d'oppressions; systéme hétérosexuel; thématiques; violences